Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the given system of equations:
1. [tex]\( x + 2y - z = 8 \)[/tex]
2. [tex]\( x + y - 2x = 0 \)[/tex]
Let's solve it step by step:
### Step 1: Simplify the Second Equation
First, take the second equation:
[tex]\[ x + y - 2x = 0 \][/tex]
Combine like terms:
[tex]\[ -x + y = 0 \][/tex]
This simplifies to:
[tex]\[ y = x \][/tex]
### Step 2: Substitute [tex]\( y = x \)[/tex] into the First Equation
Now substitute [tex]\( y = x \)[/tex] into the first equation:
[tex]\[ x + 2y - z = 8 \][/tex]
Substitute [tex]\( y \)[/tex] with [tex]\( x \)[/tex]:
[tex]\[ x + 2(x) - z = 8 \][/tex]
Simplify the terms:
[tex]\[ x + 2x - z = 8 \][/tex]
[tex]\[ 3x - z = 8 \][/tex]
### Step 3: Solve for [tex]\( z \)[/tex] in terms of [tex]\( x \)[/tex]
From the equation [tex]\( 3x - z = 8 \)[/tex], isolate [tex]\( z \)[/tex]:
[tex]\[ z = 3x - 8 \][/tex]
### Solution
The system of equations is now simplified to:
[tex]\[ y = x \][/tex]
[tex]\[ z = 3x - 8 \][/tex]
Thus, the simplified system is:
[tex]\[ y = x \][/tex]
[tex]\[ z = 3x - 8 \][/tex]
1. [tex]\( x + 2y - z = 8 \)[/tex]
2. [tex]\( x + y - 2x = 0 \)[/tex]
Let's solve it step by step:
### Step 1: Simplify the Second Equation
First, take the second equation:
[tex]\[ x + y - 2x = 0 \][/tex]
Combine like terms:
[tex]\[ -x + y = 0 \][/tex]
This simplifies to:
[tex]\[ y = x \][/tex]
### Step 2: Substitute [tex]\( y = x \)[/tex] into the First Equation
Now substitute [tex]\( y = x \)[/tex] into the first equation:
[tex]\[ x + 2y - z = 8 \][/tex]
Substitute [tex]\( y \)[/tex] with [tex]\( x \)[/tex]:
[tex]\[ x + 2(x) - z = 8 \][/tex]
Simplify the terms:
[tex]\[ x + 2x - z = 8 \][/tex]
[tex]\[ 3x - z = 8 \][/tex]
### Step 3: Solve for [tex]\( z \)[/tex] in terms of [tex]\( x \)[/tex]
From the equation [tex]\( 3x - z = 8 \)[/tex], isolate [tex]\( z \)[/tex]:
[tex]\[ z = 3x - 8 \][/tex]
### Solution
The system of equations is now simplified to:
[tex]\[ y = x \][/tex]
[tex]\[ z = 3x - 8 \][/tex]
Thus, the simplified system is:
[tex]\[ y = x \][/tex]
[tex]\[ z = 3x - 8 \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.